Assessing the Long-Term Groundwater Level Dynamics in Szigetköz, Hungary - Máté Chappon; Klaudia Madarász; Katalin Bene (Chemical Engineering Transactions)
Szigetköz, a large island in the Hungarian Upper Danube, features unique gravel subsoils ranging from 10 to 600 m thick. The region’s groundwater levels, profoundly influenced by the Danube’s flow, are crucial for drinking water, irrigation, flood retention, and ecosystem functioning. Groundwater levels also impact topsoil moisture, affecting agriculture and forestry. Throughout the 20th century, human interventions, such as river regulation and hydropower plants, disrupted the groundwater balance in Szigetköz. Over the past three decades, water replenishment systems have been implemented to mitigate these effects and restore natural water levels. This study analyses long-term groundwater data from the 1950s until 2022, utilizing over 50 monitoring wells to map fluctuations in groundwater levels. For three periods, decadal, annual, and seasonal groundwater level analyses revealed the impacts of human intervention and the impacts of revitalization. Results of this study show that in the crucial spring and summer seasons, particularly in the vulnerable central regions of Szigetköz, the water table has been elevated by an average of 20-30 cm, recovering more than one-third of the water level reduction caused by the Danube’s diversion. However, in the winter period, groundwater levels dropped further in the last 30 y in the upper areas of Szigetköz. These partly unexpected insights highlight the need for further investigations to identify the main drivers of groundwater level dynamics, including studying the effect of bed clogging and the possible consequences of restoring the water levels of the Old Danube.